The Importance of Mastering Teacher Pedagogical Competence in Improving the Quality of Education - Amaliah, Ayu; Frez Djaxxas Daleon Clorion; Pasaribu, Gumarpi (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
Education plays a crucial role in the development of a nation, with teachers as agents of change. Mastery of teacher pedagogical competence is the key to designing effective learning. However, the low achievement of student learning outcomes and teacher competence in Indonesia is still a problem. This research uses the literature study method to explore the importance of mastering teachers' pedagogical competencies in improving the quality of education. The results show that teachers' mastery of pedagogical competence plays a significant role in successful learning. Factors such as lack of education and training, as well as limited teaching experience, affect teachers' abilities. Specific strategies need to be implemented in accordance with the Teacher Pedagogical Competency Standards to improve the quality of education. Ten pedagogical competencies, including mastery of student characters and the use of technology as a learning medium, guide the improvement of education quality. Through the literature study method, this research concludes that teachers' mastery of pedagogical competencies plays a central role in improving the quality of education in Indonesia. Special attention to teacher training and development is needed to ensure they can meet professional standards and bring about positive changes in education.